The impact of fiscal decentralization on tourism development in Java Island: A study of district/city level data - Jihan Lyra Vhina; Al Muizzuddin Fazaalloh (Universitas Ahmad Dahlan, 2026)
Java Island was the center of tourism activities in Indonesia and contributed the most to national tourist activity. However, the development of tourism among regions in Java Island still showed imbalances. Significant variations between regions indicated the need for a local-based approach to maximize tourism potential. In this context, fiscal decentralization plays an important role because it gives local governments more flexibility to manage local resources and design development policies according to the characteristics of their regions. This study aimed to analyze how fiscal decentralization influenced tourism development on Java Island and whether its impact differed across tourist segments. The analysis method used in this study was panel data regression with data from districts/cities during the 2010–2023 period. The results showed that fiscal decentralization contributed positively and significantly to the total number of tourists. However, there are differences in the impact between international and domestic tourists. Fiscal decentralization did not influence international tourist arrivals, but had a positive effect on domestic tourists. These findings indicated that the mechanism of strengthening regional fiscal capacity has not been able to attract international tourists, but it effectively stimulated domestic tourist movement through improvements in public services, local infrastructure, and tourism facilities. Thus, fiscal decentralization can be positioned as a strategic policy instrument to strengthen domestic tourism performance, while the development of international tourists required the support of macroeconomic factors and cross-regional policies that are not addressed at the district/city level.